2008
DOI: 10.1152/ajprenal.00492.2007
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II stimulates elution of Na-K-ATPase from a digoxin-affinity column by increasing the kinetic response to ligands that trigger the decay of E2-P

Abstract: We earlier observed that treating rat proximal tubules with concentrations of angiotensin II (ANG II) that directly stimulate Na-K-ATPase activity changed how Na-K-ATPase subsequently eluted from an ouabain-affinity column. In this study we tested whether ANG II increases the rate of elution in response to ligands that trigger the decay of E(2)-P, which implies a change in functional properties of Na-K-ATPase, or by decreasing the amount subsequently eluted with SDS, which suggests a change in how Na-K-ATPase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(30 citation statements)
references
References 38 publications
2
28
0
Order By: Relevance
“…It has, however, never been demonstrated that Ang II-dependent phosphorylation of the Na +/ K + -ATPase can change any of the basic biochemical properties of the Na +/ K + -ATPase. We were, therefore, intrigued by the evidence that exposing rat proximal tubule cells to Ang II changes the rate at which the Na +/ K + -ATPase is released from a digoxin-affinity column in response to Na + and ATP [7], because this response means that Ang II must have changed the conformation of Na +/ K + -ATPase before it bound to digoxin. Furthermore, the Na +/ K + -ATPase in the plasma membranes from rat kidney elutes in two distinct peaks in response to different concentrations of Na + and each peak is differentially regulated by Ang II [7].…”
Section: Introductionmentioning
confidence: 99%
“…It has, however, never been demonstrated that Ang II-dependent phosphorylation of the Na +/ K + -ATPase can change any of the basic biochemical properties of the Na +/ K + -ATPase. We were, therefore, intrigued by the evidence that exposing rat proximal tubule cells to Ang II changes the rate at which the Na +/ K + -ATPase is released from a digoxin-affinity column in response to Na + and ATP [7], because this response means that Ang II must have changed the conformation of Na +/ K + -ATPase before it bound to digoxin. Furthermore, the Na +/ K + -ATPase in the plasma membranes from rat kidney elutes in two distinct peaks in response to different concentrations of Na + and each peak is differentially regulated by Ang II [7].…”
Section: Introductionmentioning
confidence: 99%
“…The samples were centrifuged at 16,000 RCF for 10 min at 4°C, and the supernatant was discarded. A volume of 0.5 ml of cold RIPA buffer containing 2% SDS and protease inhibitors (22) was added to the pellet, and the tube was vortexed for 10 min at 4°C. Another 0.25 ml of the same solution was added, and the mixing continued.…”
Section: Tissue Processingmentioning
confidence: 99%
“…The final protein concentration was ϳ4 mg/ml. An aliquot containing 0.3 mg of protein was removed, and the volume was increased to 0.5 ml by adding RIPA buffer supplemented with protease inhibitors (22). This sample was combined with 0.5 ml of immobilized streptavidin that had been previously washed twice with ice-cold RIPA buffer.…”
Section: Tissue Processingmentioning
confidence: 99%
See 2 more Smart Citations